Le famiglie migranti di bambini disabili. Progettualità e interventi educativi - Pennazio, Valentina; Armani, Samantha; Traverso, Andrea (Rivista Italiana di Educazione Familiare, 2015)
The paper presents a reflection on the difficulties that a migrant family with a child with disabilities lives when it arrives in the host country. In the paper we try to highlight: how the concept of disability is influenced by the culture of belonging; how this conception of disability can affect the acceptance or not acceptance of rehabilitative and educative actions offered to families. In addition, we want to highlight the difficulties that we may be in the promotion of a positive relationship with migrant families of disabled children, and to suggest some strategies that can be adopted in an educative context, in order to interact positively with their. Finally we analyze the difficulties that teachers face in school to achieve inclusive educational actions and we present some practical proposals like: ‘the net work’ and ‘the awareness of class group’ (necessary to accept ‘the diversity’).